Mechanical and degradation properties of poly(methyl methacrylate) cement/borate bioactive glass composites. Issue 7 (14th March 2020) - Cole, Kimberly A.; Funk, Grahmm A.; Rahaman, Mohamed N.; McIff, Terence E.
Abstract: Bone cement is used extensively in orthopedics to anchor prostheses to bone and fill voids. Incorporating bioactive glass into poly(methyl methacrylate) (PMMA)‐based bone cement could potentially improve its effectiveness for these tasks. This study characterizes the mechanical and degradation properties of composites containing PMMA‐based bone cement and particles of borate bioactive glass designated as 13‐93B3. Glass particles of size 5, 33, and 100 μm were mixed with PMMA bone cement to create composites containing 20, 30, and 40 wt % glass. Composites and a bone cement control were soaked in phosphate‐buffered saline. Compressive strength, Young's modulus, weight loss, water uptake, solution pH, and ionic concentrations were measured over 21 days. The compressive strengths of composites decreased over 21 days. Average Young's moduli of the composites remained below 3 GPa. Weight loss and water uptake of specimens did not exceed 2 and 6%, respectively. Boron concentrations and pH of all solutions increased over time, with higher glass weight fractions leading to higher pH values. Results demonstrated that the composite can sustain glass degradation and ionic release without compromising short‐term mechanical strength.